FACTORS THAT INFLUENCE THE PRODUCTIVITY OF PALM OIL HARVESTING LABOR AT PTPN IV PABATU PLANTATION - Miko Pranata Ginting; Koko Junaidi (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
Labor productivity is a critical factor in determining operational efficiency in the oil palm plantation sector. This study aims to analyze the influence of age, work experience, and wages on the productivity of harvest workers at PTPN IV Pabatu Plantation Unit. A quantitative approach was employed using multiple linear regression. A sample of 80 respondents was selected from the population of permanent harvest workers through random sampling. The results indicate that, simultaneously, the three independent variables significantly affect labor productivity. Partially, age and wages have a significant influence, while work experience does not. Wages were found to be the most dominant factor in enhancing productivity. These findings suggest the need for fair wage policies and performance-based incentive systems to improve harvesting efficiency in plantation operations.